-x=-y+2

Simple and best practice solution for -x=-y+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x=-y+2 equation:


Simplifying
-1x = -1y + 2

Reorder the terms:
-1x = 2 + -1y

Solving
-1x = 2 + -1y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-1'.
x = -2 + y

Simplifying
x = -2 + y

See similar equations:

| 18=2(3k+1)-4 | | 4x+48=12x | | x^2+10=154 | | 2.5x+6=60 | | 2y^2+3y-35= | | 8y=33-5y | | 9d-9=18 | | 9u=4u+35 | | 6m+4m-m+5=23 | | 6(x+3)-20=32 | | 3x-5x+1=8-2x | | 2x+3+0.75= | | 9y^2+18y+8= | | x^2-16x-132=0 | | 10=30(20)+b | | y=ln(x+2)-4 | | 10(x-2)+12(x+4)=x | | 9x-37=12x+23 | | -7y-2x=-13 | | 5.5x+1.2-0.3=7.2x-3 | | 13=4x?9 | | 12+x^2=8y-y^2 | | -2[3+4(x-1)]=x | | x+2x+3x=306 | | -3-66x=9 | | 5.2x=3x | | 1=2(12) | | 196-36x^2=0 | | 6x=306 | | -16x+3=37+x | | 6q+1=31 | | pq+3p= |

Equations solver categories